Evaluation of Asian Students Exchange Program (ASEP) in The Range of Building A Generation of Youth with A Global Vision - Muthi, Ibnu (Jurnal Ilmiah Global Education, 2024)
The exchange of information and culture through student exchange programs is becoming increasingly important in this era of globalization. One of them is the Asian Students Exchange Program (ASEP), which aims to evaluate the Asian Student Exchange Program at Al Azhar Islamic Middle School 9 Kemang Pratama Bekasi. Research methodology using the CIPP. Methodology is carried out to analyze the effectiveness and sustainability of the program. Through the Context, Input, Process, and Product (CIPP) approach, the evaluation provides a comprehensive understanding of the various aspects of the program, from the initial context to its long-term impact. 2) The Input Aspect indicates that the implementation guidance, program management, and participant preparation have been done well. The guidelines are available complete and understandable, the management of the program is organized effectively with clear task division, and the participant is prepared with the required qualifications. 3) The Process Aspect, in which the ASEP (Asian Students Exchange Program) program implementation is generally good enough but still needs improvement in some aspects to provide optimal benefits. 4) The Product Aspects, ASEP Program found that the participants showed a good level of independence during their homestay in Taiwan and confidence in their English presentation. As for the conclusion of the research results based on analysis and interpretation that the implementation of the ASEP (Asian Students Exchange Program) program is generally good enough but still needs improvement in some aspects in order to provide optimal benefits for schools that have this excellent program.